2009
DOI: 10.1161/hypertensionaha.108.124008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated With Circadian Blood Pressure Patterns in Hypertensive Patients

Abstract: Ambulatory blood pressure (BP) monitoring has become useful in the diagnosis and management of hypertensive individuals. In addition to 24-hour values, the circadian variation of BP adds prognostic significance in predicting cardiovascular outcome. However, the magnitude of circadian BP patterns in large studies has hardly been noticed. Our aims were to determine the prevalence of circadian BP patterns and to assess clinical conditions associated with the nondipping status in groups of both treated and untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
143
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 318 publications
(168 citation statements)
references
References 30 publications
8
143
6
Order By: Relevance
“…In our experience, the burden of cardiovascular risk was the main determinant for a blunted nocturnal BP decrease. 24,25 The contribution of the absence of a nocturnal BP fall is controversial in patients with diabetes. Absolute BP levels, particularly at night, probably have a higher predictive value for vascular damage than the BP dipper/nondipper status.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, the burden of cardiovascular risk was the main determinant for a blunted nocturnal BP decrease. 24,25 The contribution of the absence of a nocturnal BP fall is controversial in patients with diabetes. Absolute BP levels, particularly at night, probably have a higher predictive value for vascular damage than the BP dipper/nondipper status.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with a non-dipper pattern (reduction in nighttime SBP o10%) are at increased risk for cerebrovascular and cardiovascular complications Nocturnal dipping and endothelial function in resistant hypertension T Quinaglia et al when compared with individuals with a normal dipper profile. 16,[21][22][23][24][25][26] Previous studies have shown that patients with UCRH and CRH both have blunted nocturnal drops in SBP and DBP. 3,27 In these earlier publications, patients with RHTN have a high prevalence of nondipper pattern which contributes to an increased risk of cardiovascular events, 18 as well as a high prevalence of target organ damage at cardiac, macroand microvascular levels.…”
Section: Discussionmentioning
confidence: 99%
“…Details of physician recruitment and characteristics of the registry have been reported elsewhere 11, 12. Briefly, physicians and nurses received specific training in the technique of ABPM and used the internet‐based platform that receives ABPM records, together with their corresponding medical charts.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology of office BP measurements and 24‐hour ABPM has been previously described by our group 2, 4, 11, 12. Briefly, BP was measured at the office with a calibrated mercury sphygmomanometer or a validated oscillometric device, after 5 minutes rest in a sitting position.…”
Section: Methodsmentioning
confidence: 99%